Benefits of Ankle Arthroscopic Debridement in Acute and Subacute in Ankle Fractures. Issue 1 (January 2022) - Ceccarini, Paolo; Marzano, Fabrizio; di Giacomo, Lorenzo; Rinonapoli, Giuseppe; Caraffa, Auro
Category: Ankle; Arthroscopy; Trauma Introduction/Purpose: The purpose of this study was to evaluate the benefits of ankle arthroscopy at the time of ORIF or after six months in patients with residual symptoms. The hypothesis was that in patients treated arthroscopically at the time of ORIF, there were faster and better clinical results than those treated after or untreated with arthroscopy. Methods: In this retrospective study, we compared three homogeneous groups of selected patients with specific inclusion criteria (144in total, mean age 38.2 years). They have been surgically treated for an ankle fracture (bimalleolar or trimalleolar without frank syndesmotic injuries) with open technique (ORIF) or arthroscopic ORIF (AORIF), between 2016 and 2019. The AO classification system was used for each patient. The clinical assessment was based on the Foot and Ankle Outcome Score (FAOS). Results: At the final follow-up (mean 36 months), both patients treated with ankle arthroscopic debridement at the time of ORIF and patients treated with arthroscopic debridement after ORIF showed a significant improvement of the FAOS, which reported84 and 85 respectively at final follow-up. Conclusion: Through direct visualization of intra-articular structures, ankle arthroscopy can offer an essential option for patients both in acute and in sequelae after an ankle fracture. More studies are needed to understand the real effectiveness of the procedure, especially in acute at the same time of osteosynthesis.